Search for flavour-changing neutral current interactions of the top quark and the Higgs boson in events with a pair of τ-leptons in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
Abstract: A search for flavour-changing neutral current (FCNC) tqH interactions involving a top quark, another up-type quark (q = u, c), and a Standard Model (SM) Higgs boson decaying into a τ -lepton pair (H → τ +τ −) is presented. The search is based on a dataset of pp collisions at √s = 13 TeV that corresponds to an integrated luminosity of 139 fb−1 recorded with the ATLAS detector at the Large Hadron Collider. Two processes are considered: single top quark FCNC production in association with a Higgs boson (pp → tH), and top quark pair production in which one of top quarks decays into W b and the other decays into qH through the FCNC interactions. The search selects events with two hadronically decaying τ -lepton candidates (τhad) or at least one τhad with an additional lepton (e, μ), as well as multiple jets. Event kinematics is used to separate signal from the background through a multivariate discriminant. A slight excess of data is observed with a significance of 2.3σ above the expected SM background, and 95% CL upper limits on the t → qH branching ratios are derived. The observed (expected) 95% CL upper limits set on the t → cH and t → uH branching ratios are 9.4 × 10−4 (4.8+2.2−1.4 × 10−4) and 6.9 × 10−4 (3.5+1.5−1.0 × 10−4), respectively. The corresponding combined observed (expected) upper limits on the dimension-6 operator Wilson coefficients in the effective tqH couplings are Ccφ < 1.35 (0.97) and Cuφ < 1.16 (0.82).